GREEN BEAUTY REVOLUTION: HOW IMPORTANT IS THE ROLE OF SOCIAL MEDIA IN SHAPING PURCHASE INTENTION IN THE INDONESIAN COSMETICS INDUSTRY? - Ananda, Aditia Rajwita Rizki; Munawaroh, Siti; Kurniawati, Kurniawati (Universitas Nusa Cendana, 2025)
Cosmetic products have become an essential part of Indonesian women's routines. However, the recent use of cosmetics has a low environmental impact. The research uses the non-probability sampling method with the purposive sampling technique. Sampling was distributing questionnaires to 246 respondents who are consumers of eco-friendly cosmetic products. Hypothesis testing was performed using structural equation modeling with the support of AMOS24 software. These findings underline the important role of brand equity, which is influenced by social media usage, brand awareness, and brand image. And then have a significant influence on purchase intentions, especially in the eco-friendly cosmetic industry. However, this study has not explored the effectiveness of various platforms, interaction frequencies, and specific content types. To strengthen brand equity and influence purchase intention, further research suggests exploring this and adding other variables, such as product innovation, customer relationships, and brand value. Keywords: Social Media Usage; Brand Awareness; Brand Image; Brand Equity; Purchase Intention